Penerapan Model Project Based Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Kearsipan Kelas X OTKP SMKN 2 Tuban - Dewi Asrilika Suryani; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This study aims to describe the application of the Project-Based Learning model and analyze the Project-Based Learning model to the learning outcomes of the X-Grade OTKP subjects in SMKN 2 Tuban. This type of research is experimental research using quasi-experimental. The population in this study were class X OTKP 1, class X OTKP 2, class X OTKP 3, and class X OTKP 4 as many as 144 students, while the sample in this study was class X OTKP 1 and class X OTKP 2 as many as 72 students each each number of students 36. The research instrument consisted of tests conducted with 20 items. Data analysis techniques include: 1) item analysis in accordance with the validity test, reliability test, difficulty level test, and distinguishing power test; 2) normality test; 3) homogeneity test, and 4) hypothesis testing. The results showed that the results of the test analysis showed Ho was rejected and Ha was accepted with a significance level of 0.00 which was less than 0.05. From this it can be seen that there is an effect of the Project Based Learning model on learning outcomes subject Record Management for class X student OTKP SMKN 2 Tuban.